2016
DOI: 10.1002/mus.25367
|View full text |Cite
|
Sign up to set email alerts
|

Progress and challenges in diagnosis of dysferlinopathy

Abstract: Dysferlin-deficient limb girdle muscular dystrophy type 2B, distal Miyoshi myopathy, and other less frequent phenotypes are a group of recessive disorders called dysferlinopathies. They are characterized by wide clinical heterogeneity. To diagnose dysferlinopathy, a clinical neuromuscular workup, including electrophysiological and muscle imaging investigations, is essential to support subsequent laboratory testing. Increased serum creatine kinase levels, distal or proximal muscle weakness, and myalgia with ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
100
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 158 publications
(255 reference statements)
1
100
0
8
Order By: Relevance
“…LGMD have more than 30 different subtypes linked to specific gene loci, which manifest in very overlapping and heterogeneous phenotypes 1, 2, 3. This is likely the result of a tight link between associated muscle proteins within the sarcomere‐sarcolemma‐sarcoplasm‐extracellular‐matrix network (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…LGMD have more than 30 different subtypes linked to specific gene loci, which manifest in very overlapping and heterogeneous phenotypes 1, 2, 3. This is likely the result of a tight link between associated muscle proteins within the sarcomere‐sarcolemma‐sarcoplasm‐extracellular‐matrix network (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of progression can be quite variable with some individuals progressing rapidly over a few years to being non-ambulatory, however one-third of affected cases were found wheelchair bound after 10 years of onset 21. Katz et al22 described patients with a Miyoshi phenotype that did not have a primary dysferlinopathy. These patients differed from those with dysferlinopathy by their later age of onset (usually after 30 years of age) and discreetly raised serum CK level 22.…”
Section: Discussionmentioning
confidence: 99%
“…Katz et al22 described patients with a Miyoshi phenotype that did not have a primary dysferlinopathy. These patients differed from those with dysferlinopathy by their later age of onset (usually after 30 years of age) and discreetly raised serum CK level 22. In the present study, the clinical phenotype of Miyoshi myopathy is consistent with already reported phenotypes 4,8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysferlin enhances calcium-mediated membrane fusion and sarcolemmal repair. 3 Targeted sequencing remains the gold standard in the precise diagnosis of dysferlinopathy. 2 Predominantly, proximal and distal muscles are implicated in dysferlinopathy which is most pronounced in the pelvic and shoulder girdle muscles (Limbgirdle muscular dystrophy type 2B, LGMD2B), or in distal parts of the legs involving either the gastrocnemius and soleus muscles in cases of Miyoshi myopathy (MM), or the anterior tibial muscles, as in distal anterior compartment myopathy (DACM).…”
Section: Introductionmentioning
confidence: 99%